ACTION OF CHAMOMILE - Matricaria recutita L. FOR COLICS IN NEONATES: narrative review - Vaz, Nathalya Cristina (2021)
The aim of this work was to review the bibliography on the use of Chamomile (Matricaria recutita L.) for colic in infants. The research design was a narrative bibliographic review based on articles published since 1980. The search words used were: colic, infants, chamomile. Studies have shown that the effect of chamomile in the treatment of colic is related to its antispasmodic property. Since there may be a large amount of gas produced in the intestine of colicky babies, chamomile may exert its antiflatulent effect in response to this complication. However, studies are rare and with a low sample number, although the plant has shown some effectiveness. Thus, the professional indication of chamomile in vehicles, pharmaceutical forms and adequate concentrations can be an option to treat infantile colic. However, there is a contraindication to use teas for at least 6 months of the infant's life. Infantile colic has a prevalence of 10 to 20% and is one of the most common problems in the neonatal period. It is characterized by loud crying and sudden restlessness, usually occurring at dusk at night. According to Wessel's Triple Law, involving crying and fussing for more than 3 hours a day, for more than 3 days a week, and for more than 3 weeks. The etiology of colic is unknown and usually resolves within 3 to 4 months spontaneously. Treatment options are described, from behavioral measures, massage techniques, use of medication and plants, but with still controversial results and effectiveness.